EFFECT OF PARTIAL REPLACEMENT OF COW MANURE IN LIQUID FERTILIZER WITH CORN WASTE IN VARIOUS SOIL TYPES ON THE GROWTH AND YEARS OF Asystasia gangetica (L.) subsp. Micrantha - I K. A. U., Wahyudi; Duarsa, M. A. P.; Kusumawati, N. N. C. (Jurnal Peternakan Tropika; Vol 12 No 1 (2024): Vol. 12 No. 1 Tahun 2024; January - February, 2024)
This study aims to determine the effect of replacing part of the cow dung in liquid fertilizer with chopped corn waste in various types of soil on the growth and yield of Asystasia gangetica (L.) subsp. Micrantha. This research was conducted in a greenhouse, Jalan Raya Sading number 93, Mengwi, Badung, Bali. The research lasted for 3 months from preparation to cutting. The study used a completely randomized design with a split-plot pattern with two factors. The first factor is the main plot, namely the type of soil consisting of Mediteran soil (T1) obtained in Jimbaran, Regosol soil (T2) obtained in Pengotan, and latosol soil (T3) obtained in Sobangan. The second factor was the type of liquid fertilizer which consisted of liquid cow manure without treatment (P1), liquid cow manure + EM4 (P2), liquid cow manure + EM4 + corn plant waste (P3). There were 9 treatment combinations and each treatment was repeated four times so there were 36 experimental units. The variables observed were growth variables, yield variables and plant growth characteristics variables. The results showed that there was no interaction between replacing cow dung in liquid fertilizer and chopped corn waste in various types of soil in all variables. The use of sobangan soil tended to provide the highest average compared to jimbaran and pengotan soils which statistically showed results that were not significantly different for all variables except leaf dry weight. On the leaf dry weight variable, Asystasia gangetica (L.) subsp. Micrantha planted on latosol soil (T3) gave significantly different results from mediteran soil. In other variables, the three types of soil did not give significantly different results, however, sobanan soil tended to give the highest average. Treatment of liquid cow manure + EM4 gave the highest average but not significantly different from cow manure + EM4 + corn flakes on the growth and yield of Asystasia gangetica (L.) subsp. Micrantha. From the results of the study it can be concluded that latosol soil type gives the best results and chopped corn waste can replace some of the cow dung in liquid fertilizer on the growth and yield of Asystasia gangetica (L.) subsp. Micrantha.